Review of The Institutional View on The Liberalization and Management of Capital Flows : Background Note on Using the IPF Analytical Toolkit to Enhance Policy Assessments - Kolasa, Marcin (Policy Papers; Policy Paper, 2022)
Insights from the IPF workstream can help guide the appropriate policy mix during an inflow surge, based on the shock and country characteristics. Inflow surges may be caused by a range of shocks and can take different forms in different countries. The IPF models suggest that warranted macroeconomic policy adjustments depend on the nature of the shock and country characteristics. The IPF models point to shocks and country characteristics that make it difficult to effectively respond to surges using only macroeconomic policy and exchange rate adjustment. The IPF models also suggest that, in the presence of overheating and overvaluation, the use of FXI and CFMs can enhance monetary autonomy in certain circumstances without generating other distortions. The relative costs and benefits of FXI and CFMs depend on country-specific factors. The IPF models also illustrate how surges can lead to a build-up of systemic financial risks. The IPF workstream connects the appropriate mix of MPMs and CFM/MPMs to the structure of the country's financial system.